The concept of the national information platform of biobanks of the Russian Federation - A. N. Meshkov; O. Yu. Yartseva; A. L. Borisova; M. S. Pokrovskaya; O. M. Drapkina (Кардиоваскулярная терапия и профилактика)
Aim. To create the concept of the national information platform of biobanks of the Russian Federation (NIPB RF).Material and methods. In April 2022, an expert group consisting of 17 representatives of Russian biobanks was formed in National Association of Biobanks and Biobanking Specialists to create the concept of the NIPB RF. An analysis of international practices in this area was carried out. To assess the infrastructure of Russian biobanks in terms of information support for stored biomaterial, experts formed a questionnaire consisting of several blocks of questions. The survey was conducted from April to June 2022 among representatives of Russian biobanks. Descriptive statistics were used to analyze the results of the survey.Results. In total, representatives of 16 biobanks took part in the survey. The storage capacity of biobanks varies from 2000 to 800000 storage units. It is shown that the majority of biobanks (81%) use information systems for entering and storing related data. Biobanks use foreign and Russian software products (53 and 47%, respectively), while a  third develop their own information systems. We formulated the NIPB RF concept as an information system designed for consolidating, processing and using data on biosamples for the development of Russian biobanking and improving the efficiency and quality of research.Conclusion. The creation of the NIPB RF will improve the interaction between biobanks and end users and will develop biomedicine in Russia.